Analisis standard hotel mesra Muslim di Malaysia berdasarkan perspektif Maqasid Syariah - Mohammad Zaini Yahaya,; Muhammad Adib Samsudin,; Mohd Izhar Ariff Mohd Kashim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaysia is far advanced in introducing the Muslim friendly hotel segment as an Islamic tourism product. Malaysian hoteliers refer to three standards when offering Muslim friendly hotel services, which are namely the MS 2610: 2015 Muslim Friendly Hospitality Services Requirements, Crescent Rating Standard and Salam Standard. Moreover, CrescentRating Standard and Salam Standard have become standards for assessing Muslim friendly hotels at the international level. This study evaluated these standards in terms of their adherence to the Maqasid Syariah principle. Criteria for fulfilling these standards were presented and analyzed according to the five kulliyyat found in the Maqasid Syariah, such as protection of religion, life, intelect, lineage and wealth. Findings show that these standards strongly emphasize criteria related to safeguarding religion, such as performing prayers and fasting; safeguarding lives, such as consuming halal food; safeguarding the mind, such as abstaining from consuming alcohol beverages as well as safeguarding familial lineage, such as separating individuals according to their gender in swimming pools and spas. However, safeguarding lives, from the self-security aspect, and safeguarding property were not part of the criteria that determines the standards even though both these criteria are the fundamental needs of hotel guests. The failure to include these criteria has made these standards lose their holistic nature as well as become incapable of becoming evaluating standards that are completely detached from contemporary conventional standards.